Islamic Education Curriculum Development: Muhammad Iqbal's Thoughts on Progressive Islamic Education - Diana, Diana; Shapawi, Ahmad Muzammil Mohamed (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2024)
This research examines Muhammad Iqbal's thoughts on the development of Islamic education curriculum with a focus on the integration of science and religion in contemporary education. The background of this research is the need for curriculum renewal that is relevant to the advancement of modern knowledge and the needs of society. The research method used is descriptive-analytical literature review by collecting and analyzing Iqbal's works and other related literature. The findings of the research show that Iqbal advocated a holistic education, combining Islamic spiritual values with scientific knowledge and humanities to create a comprehensive curriculum that meets the demands of the times. The study suggests that Iqbal's approach can serve as a basis for designing an Islamic education curriculum that produces graduates with balanced intellectual, spiritual, and social skills who are ready to contribute to the development of a dynamic and inclusive society.